Ta’thīr Istikhdām Wasīlah Scrabble fī Tarqiyyati Itqāni Al- Mufradāt Ladá Al-Ṭullāb bi Al-Madrasah Al-Mutawassiţah Al-Islāmiyyah Al-Ḥukūmiyyah 6 Agam - Riti Hariati; Oktarina Yusra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Researchers found several problems in the process of learning vocabulary for 7th grade students at MTSN 6 Agam. Most students found it difficult to memorize the vocabulary and to master it. There are interesting learning media that can be taught during students learning vocabulary. In this study, the researchers used experimental quantitative research with a true experimental design using pretest-posttest control group design. The total populations were 155 students and the samples were 63 students using a random sampling technique. The data analysis technique used statistical analysis using spss20. The results of the study showed that there was the effect of using scrabble media on increasing students' vocabulary mastery. The average post-test score for the experimental class was 67.5 and the average for the pretest for the control class was 60.48. And the researcher found 2 tailed sig values 0.44 and 0.46, and both values were smaller than 0.05. So it can be concluded that there were differences between the two classes.وجدت الباحثة المشكلات في تعليم المفردات لدى طلّاب الفصل السّابع بالمدرسة المتوسّطة الإسلاميّة الحكوميّة 6 آغام. كثير من الطّلّاب يشعرون بصعوبة في حفظ المفردات وفي ترقيّة إتقانها. ولم توجد الوسائل التّعليميّة الجذابة في تعليم المفردات. الطريقة المستخدمة في هذا البحث هي طريقة كمية باستخدام مدخل شبه تجربة بنوع مقارنة البحث بين الفصل التجريبي والفصل الضابط True Eksperimental Designبالنّوع Pretest-Posttest Control Group Design. نتائج البحث هي هناك تأثير استخدام وسيلة سكرابل على ترقيّة إتقان المفردات. كانت نتيجة حساب متوسّط الاختبار البعدي في الفصل التّجريبي 67،5 وأمّا نتيجة حساب متوسّط الاختبار القبلي في الفصل الضّابط 60،48. وتوجد قيمة الأهميّة (Sig 2-Tailed)0،44 و0،46 أصغر من 0،05. و تخلص أنّ هناك فرقا بين الفصلين.